1969
DOI: 10.1002/macp.1969.021260115
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of crystalline poly(p‐phenylene oxides) I. Poly(p‐phenylene oxide)

Abstract: Using X-ray diffraction the structure of crystalline poly(p-phenylene oxide), 9 has been determined. The unit cell is orthorhombic, with the dimensions: a = 8.07 A, b = 5.54 A, and c (fiber axis) = 9.72 A. The unit cell contains four monomeric units. TWO molecular chains pass through a unit cell, one through the center, the other through a corner. Two monomeric units are contained in the fiber identity period. The space group is Pbcn -0:;. The oxygen atoms and the centers of gravity of the phenylene groups are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
30
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(42 citation statements)
references
References 11 publications
12
30
0
Order By: Relevance
“…Furthermore the ring conformation at the global minimum was, in each case, close to that obtained in X-ray studies. Thus for PEK the calculated value of ~ 32 ° compares with an observed twist angle of 34 ° [4] whilst in PE the approximate experimental value of about 40 ° [1] is in reasonable agreement with the calculated twist angle of 36-38 °. The energy differences between the calculated and experimental minima are, in each case, very small.…”
Section: (B) Energy Minima In the Pe And Pek Crystalssupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore the ring conformation at the global minimum was, in each case, close to that obtained in X-ray studies. Thus for PEK the calculated value of ~ 32 ° compares with an observed twist angle of 34 ° [4] whilst in PE the approximate experimental value of about 40 ° [1] is in reasonable agreement with the calculated twist angle of 36-38 °. The energy differences between the calculated and experimental minima are, in each case, very small.…”
Section: (B) Energy Minima In the Pe And Pek Crystalssupporting
confidence: 72%
“…Poly(phenylene oxide), PE [1], poly(aryl ether ketone), PEK [2][3][4] and poly(aryl ether ether ketone), PEEK [5][6][7][8] (Fig. 1) have broadly similar crystal structures but exhibit some differences in the unit cell parameters, ring conformations and structural variation with temperature.…”
Section: Introductionmentioning
confidence: 99%
“…PPO is known to have a crystal structure very like that of PPS; 6 thus it is tempting to attribute the difference in results to the lack of low lying d-orbitals in the oxygen derivative. This argument is complicated, however, by the known greater ease of oxidation of organosulfur compounds compared to their oxygen analogs.…”
Section: -8-mentioning
confidence: 99%
“…these systems are expected to be more flexible than the parent poly(p-phenylene) and perhaps to display better processing characteristics. 6 and poly(p-phenylene sulfide) (X=S) 7 are soluble polymers with well defined glass transition temperatures and melting points. We now find that poly(p-phenylene sulfide) (PPS) is also capable of being doped to high levels of conductivity using the strong electron acceptor arsenic pentafluoride.…”
Section: Introductionmentioning
confidence: 99%
“…[1] They pointed out that the crystal structures of PEK and PEEK are similar to that of poly(phenylene oxide) (PPO). [2] After that, many studies on the crystal structures of PEEK and the related polymers of PAEKs were performed. [3 -13] It has been shown that the chains in PEEK crystals adopt an extended conformation with the phenylene rings alternating an angle of ca.…”
Section: Introductionmentioning
confidence: 99%